2023
DOI: 10.1302/2633-1462.41.bjo-2022-0151.r1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unlinked total elbow arthroplasty for rheumatoid arthritis in patients younger than 50 years old

Abstract: Aims There are concerns regarding complications and longevity of total elbow arthroplasty (TEA) in young patients, and the few previous publications are mainly limited to reports on linked elbow devices. We investigated the clinical outcome of unlinked TEA for patients aged less than 50 years with rheumatoid arthritis (RA). Methods We retrospectively reviewed the records of 26 elbows of 21 patients with RA who were aged less than 50 years who underwent primary TEA with an unlinked elbow prosthesis. The mean pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…During a mean follow-up period of 13.6 years, there were no revisions of implant removal and no radiological evidence of loosening around the components; they reported a 25-year survival rate of 78.1% with any revision surgery as the endpoint. 20 Kondo et al reported favorable long-term clinical results of the MNSK system in 75 patients, with a 5-year postoperative survival rate of 97% and a 10-year survival rate of 93%. While good long-term results have been achieved, complications are not uncommon.…”
Section: Development Of Unlinked Type Tea and Surgical Results In Japanmentioning
confidence: 99%
“…During a mean follow-up period of 13.6 years, there were no revisions of implant removal and no radiological evidence of loosening around the components; they reported a 25-year survival rate of 78.1% with any revision surgery as the endpoint. 20 Kondo et al reported favorable long-term clinical results of the MNSK system in 75 patients, with a 5-year postoperative survival rate of 97% and a 10-year survival rate of 93%. While good long-term results have been achieved, complications are not uncommon.…”
Section: Development Of Unlinked Type Tea and Surgical Results In Japanmentioning
confidence: 99%
“… 1 TJR can alleviate pain symptoms and improve joint function and quality of life in patients who have advanced rheumatoid arthritis (RA). 2 , 3 However, due to the immune dysfunction in RA patients and their use of disease-modifying antirheumatic drugs (DMARDs), 4 , 5 the infection rate after TJR in patients who have RA can be three-times higher than that in patients who have osteoarthritis (OA), with infection rates of 4.2% and 1.4%, 6 respectively. Indeed, RA is considered to be an independent risk factor for PJI.…”
Section: Introductionmentioning
confidence: 99%